Ketaatan Negara Terhadap Hukum Perdagangan Internasional - Musfala Yudha; Nur Qalbi Putri Ramadhani Ahmad; Muhammad Agung (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
International trade law is part of international law. Therefore, of course, various imperfections or weaknesses in international law are also affected in the field of international trade law. This journal will explain why countries in conducting international trade need to comply with international trade law. This article provides an argument that the reason for a country to comply with international trade law is due to the belief that obedience will benefit the interests of the country itself. The next reason is that there is a fundamental principle within the scope of international agreements which is the legal source of international trade law, namely the principle of good faith. A country that has been bound in an international trade agreement must carry out the provisions of the agreement in accordance with the contents, soul, intent and purpose of the agreement itself, respecting the rights and obligations of each party.